Analisis Struktural dan Nilai Sosial Budaya dalam Cerpen Mamadu Ngajak Leak karya I Ketut Sandiyasa - Ni Kadek Mira Sugiarti; Ni Kadek Arisanthi; Ketut Devina Astriani (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2023)
Along with the development of the era, literary works began to develop, so that modern Balinese literary works appeared which were created to be better known by young people, especially short stories. Mamadu Ngajak Leak's short story is one of the modern Balinese short stories in a collection of short stories by I Ketut Sandiyasa. This paper describes the structural elements contained in the short story Mamadu Ngajak Leak. The short story contains important values, especially socio-cultural values ​​that we can use as guidelines for behaving and living in society. Likewise with the short content, the story of black magic or leak in the short story is very closely related to the life of today's society, so it is very interesting to know the values ​​contained therein, especially the character values ​​of the characters and their socio-cultural values. This research is a qualitative research and the method used is descriptive method. Based on the above thoughts, this study will discuss the analysis of structural elements and socio-cultural values ​​in the short story mamadu ngajak leak by I Ketut Sandiyasa.